2013
DOI: 10.5194/bg-10-67-2013
|View full text |Cite
|
Sign up to set email alerts
|

Sediment community responses to marine vs. terrigenous organic matter in a submarine canyon

Abstract: Abstract. The Whittard Canyon is a branching submarine canyon on the Celtic continental margin, which may act as a conduit for sediment and organic matter (OM) transport from the European continental slope to the abyssal sea floor. In situ stable-isotope labelling experiments were conducted in the eastern and western branches of the Whittard Canyon, testing short-term (3-7 days) responses of sediment communities to deposition of nitrogen-rich marine (Thalassiosira weissflogii) and nitrogen-poor terrigenous (Tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 89 publications
5
51
0
Order By: Relevance
“…However, the ranking of the second and third most abundant taxa varied between branches and were respectively Sipunculida (12.5%) and Bivalvia (8.4 %) in the western branch; Isopoda (16.2 %) and Tanaidacea (7.3 %) in the eastern middle branch; Isopoda (10.7 %) and Bivalvia (8.6 %) in the eastern branch. Hunter et al (2013) also noted a difference in macrofaunal composition between canyon branches at 3500 m. In the eastern branch macrofaunal-sized nematodes (> 50 %) and polychaetes (cirratulids and spionids) contributed most to the assemblage, whereas in the western branch crustaceans (tanaids and harpacticoid copepods) and polychaetes dominated. The differences between the two studies may reflect the sampling gear and sampling processing techniques used.…”
Section: Gunton Et Al (2015b) Also Found That the Whittard Canyon Mamentioning
confidence: 82%
See 3 more Smart Citations
“…However, the ranking of the second and third most abundant taxa varied between branches and were respectively Sipunculida (12.5%) and Bivalvia (8.4 %) in the western branch; Isopoda (16.2 %) and Tanaidacea (7.3 %) in the eastern middle branch; Isopoda (10.7 %) and Bivalvia (8.6 %) in the eastern branch. Hunter et al (2013) also noted a difference in macrofaunal composition between canyon branches at 3500 m. In the eastern branch macrofaunal-sized nematodes (> 50 %) and polychaetes (cirratulids and spionids) contributed most to the assemblage, whereas in the western branch crustaceans (tanaids and harpacticoid copepods) and polychaetes dominated. The differences between the two studies may reflect the sampling gear and sampling processing techniques used.…”
Section: Gunton Et Al (2015b) Also Found That the Whittard Canyon Mamentioning
confidence: 82%
“…(2015b) used a megacorer and a 300 μm sieve, whereas Hunter et al (2013) used ROV push cores and a 250 μm sieve. A megacorer will collect a larger sediment sample, while a larger sieve would retain fewer animals.…”
Section: Gunton Et Al (2015b) Also Found That the Whittard Canyon Mamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that this feature hosts increased foraminiferal (Duros et al, 2011) and nematode (Ingels et al, 2011) abundances compared with the open slope. Hunter et al (2013) reported high macrofaunal abundances inside the canyon. Duineveld et al (2001) reported a significantly higher macro-and mega-faunal biomass inside the canyon compared with the slope, but no significant difference in macrofaunal abundance.…”
Section: Introductionmentioning
confidence: 96%